2017
DOI: 10.12669/pjms.336.13373
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of C-kit protein (CD117) expression in differentiating adenoid cystic carcinoma and polymorphous low grade Adenocarcinoma

Abstract: Background & Objective:To evaluate usefulness of immunohistochemical marker C-kit (CD117) in differentiating Adenoid cystic carcinoma (AdCC) from Polymorphous low-grade adenocarcinoma (PLGA) in patients of salivary gland carcinomas. AdCC is a malignant salivary gland neoplasm with poor prognosis. PLGA is a salivary gland malignancy with indolent growth pattern. Differentiating between the two entities is a diagnostic challenge. We evaluated the role of C-kit in differentiating the two.Methods:This is a Cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…The observed genomic aberrations and overexpression of AR, KIT, and EGFR, PTEN, p-mTOR, and PDGFRA in PGC in this analysis are in keeping with previous studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The rationale for the therapy recommendation with ADT was corroborated by a study by Boon et al They studied the application of ADT in 35 patients with androgen receptor-positive advanced salivary duct carcinoma, which lead to a median overall survival (OS) of 17 months versus 5 months in 43 patients receiving best supportive care [34].…”
Section: Discussionsupporting
confidence: 91%
“…The observed genomic aberrations and overexpression of AR, KIT, and EGFR, PTEN, p-mTOR, and PDGFRA in PGC in this analysis are in keeping with previous studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The rationale for the therapy recommendation with ADT was corroborated by a study by Boon et al They studied the application of ADT in 35 patients with androgen receptor-positive advanced salivary duct carcinoma, which lead to a median overall survival (OS) of 17 months versus 5 months in 43 patients receiving best supportive care [34].…”
Section: Discussionsupporting
confidence: 91%
“…A similar result was compatible with the work of Salehinejad et al [18]. Who clarified the role of mutated c-kit as a promotor for this tumor; on the contrary, it was disagreement with Tariq et al [19], who found c-kit immunoexpression may be used as a helpful marker to distinguish AdCC from PAC in cases where the diagnosis can be challenging. In this light, a distinct pattern of c-kit immunostaining can also be a proper ancillary method for further differentiation between both tumors, as noticed in our results.…”
Section: Figure 3: a Case Of Mucoepidermoid Carcinoma Revealing Posit...supporting
confidence: 88%
“…Cancer stem cells (CSCs) are a special subpopulation of cancer cells, which are responsible for the major capabilities of self-renewal and uncontrolled proliferation and dif-ferentiation, and increasing evidence suggests that CSCs contribute to cancer metastasis, a worse prognosis, and resistance to chemotherapy or radiation therapy [5][6][7]. Cluster of differentiation 117 (CD117), termed c-kit proto-oncogene, encoded by the c-kit gene, and located on human chromosome 4q11-12, belongs to a type-III transmembrane receptor tyrosine kinase [8,9]. CD117 could act as a receptor for stem cell factor and plays an important role in maintaining cellular and biological functions such as cell survival, metabolism, cell growth and progression, proliferation, apoptosis, cell migration, cell differentiation, cell adhesion, and chemotaxis [10,11].…”
Section: Introductionmentioning
confidence: 99%